Pelatihan Eco Print Teknik Steaming (Kukus) untuk Ibu PKK Desa Lambangan Kecamatan Wonoayu Kabupaten Sidoarjo Jawa Timur - Herman Sugianto; Sepbianti Rangga Patriani; Tantra Sakre; Suparman Suparman; Ika Ismurdiyahwati; Garcia Iktia (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The Community Service Program (PPM) implemented by the Fine Arts Education Study Program of PGRI Adi Buana University Surabaya aims to provide solutions to the problems faced by PKK women in Lambangan Village, Wonoayu, Sidoarjo. The problem identified is the lack of skills in utilizing abundant natural materials, such as leaves and flowers, to produce creative handicraft products. One of the potentials that has not utilized optimally is the processing of these natural materials into eco print crafts. In fact, eco print has a fantastic opportunity to improve people's skills and provide additional economic value to support family income. As a solution, this PPM activity focuses on providing training on eco printing techniques with the steaming method to PKK women. The training conducted in a structured manner in three meetings to ensure that all participants acquired adequate knowledge and skills. The training material includes a basic understanding of eco print, material processing techniques, and firsthand practice of making products. With this approach, it hoped that participants will not only be able to produce eco-print-based artworks but also have the potential to develop handicraft businesses in the future. The results of the activity showed an increase in the ability of participants to process natural materials into handicraft products that have aesthetic and economic value. In addition, this activity succeeded in providing motivation for PKK women to utilize the potential of the surrounding environment more creatively and productively. Thus, this program contributes to the development of community skills, especially in supporting women's empowerment and improving family welfare in Lambangan Village.